Influence of Human Resource Planning on Employee Performance at the District Court Office of Gunungsitoli - Lahagu, Amila; Lase, Delipiter; Buulolo, Nanny Artatina; Mendrofa, Syah Abadi (ProBisnis : Jurnal Manajemen, 2024)
The objectives of this research are 1) To find out whether there is an influence of HR planning on employee performance. 2) To find out how much influence HR planning has on employee performance. The research method used in this research is a quantitative research method. The research results and conclusions are: (1) This research produces valid and reliable data, as proven by the results of the Validity Test with a Sig. less than 0.05 and Cronbach's Alpha Reliability Test with a value of more than 0.6. Apart from that, the data also shows a normal distribution based on the results of the Kolmogorov-Smirnov test with Asymp values. Sig. of 0.151. (2) The absence of autocorrelation and heteroscedasticity problems in the data, which is proven through Test Runs and scatterplot patterns, strengthens the reliability of statistical analysis. The Determination Coefficient (R Square) of 0.700 indicates that around 70% of the variation in Employee Performance can be explained by HR Planning Variables. The other 30% is influenced by other factors that have not been examined in this study. (3) The results of the t test show that there is a significant influence of HR Planning on Employee Performance, with a significance value (0.000) smaller than 0.05 which indicates the null hypothesis (H0) is rejected and the alternative hypothesis (Ha) is accepted. This is also supported by the results of a simple linear regression test which shows that the regression model used is valid for predicting the effect of HR Planning on Employee Performance.